Traditional agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Understandinq Traditional Agriculture: A bibliography for development workers / Carlier, H., 1987. ILEIA. 114 pp.